TOI-6695: a pair of near-resonant massive planets observed with TESS from the WINE Survey* - Eberhardt, Jan; Trifonov, Trifon; Henning, Thomas; Tala Pinto, Marcelo; Brahm, Rafael; Jordán, Andrés; Espinoza, Nestor; Jones, Matías I.; Hobson, Melissa J.; Rojas, Felipe I.; Schlecker, Martin; Acuña, Lorena; et al. (The astronomical journal, 2025)
We present the discovery and characterization of a pair of warm Jovian-mass exoplanets orbiting the Sun-like star TOI-6695, based on Transiting Exoplanet Survey Satellite (TESS) transits and precise radial velocity (RV) measurements obtained with FEROS, HARPS, CHIRON, CORALIE, and PFS. The transiting exoplanet TOI6695b has an orbital period of ∼80.4 days, a radius of 0.85Rjup, and a mass of 0.21Mjup. The outer planet has a minimum mass of 1.45Mjup and an orbital period of about 242.4 days, conﬁdently constrained by the Doppler timeseries data. The TOI-6695 exoplanet system exhibits transit-timing variations due to the dynamical interaction of the planets, which reside near a 3:1 mean-motion resonance. We modeled the TOI-6695 system’s orbital and dynamical conﬁguration by performing self-consistent N-body ﬁts of TESS photometry, ground-based photometry from Observatoire Moana, and precise RV data, all of which are consistent with the presence of a warm Jovianmass duo of exoplanets.